Temporal trends in dietary creatine intake from 1999 to 2018: an ecological study with 89,161 participants - Darinka Korovljev; Nikola Todorovic; Valdemar Stajer; Sergej M. Ostojic (Taylor & Francis Group, 2021)
Introduction We described here the annual variations in mean dietary creatine intake from 1999 to 2018 in U.S. children and adults using National Health and Nutrition Examination Survey (NHANES) database. Methods Dietary intake information from ten consecutive rounds of NHANES (from 1999 to 2000 to 2017-2018) was extracted for a total of 89,161 respondents aged 0-85 years. Individual values for total grams of creatine consumed per day were computed using the average amount of creatine (3.88 g/kg) across all creatine-containing food sources. Results The average daily intake of creatine across the entire sample was 0.70 ± 0.78 g (95% confidence interval [CI], from 0.69 to 0.71) and 13.1 ± 16.5 mg/kg body weight (95% CI, from 13.0 to 13.2). A significant negative trend for dietary creatine intake was found in infants (r = − 0.019; P = 0.042), and children and adolescents (r = − 0.024; P < 0.001). Conclusions Our findings suggest a variation in dietary creatine intake in the U.S. population during the past 20 years, with young persons tend to consume fewer grams of creatine per day from 1999 onwards. Long-running studies are highly warranted to assess possible health consequences of variable creatine intake in human nutrition.